Antibacterial Activity of some Fresh Water Algae - A.M. Chavan2, S.M. Kamble1* and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Present deals with the study of antibacterial activity of some fresh water algae against some bacteria. It was found that some fresh water algae showed antibacterial activity. ——————————————————————————————————– 1Department of Botany, Sangmeshwar College, Solaphur (M.S.), India; 2Department of Botany Dr. Babasaheb Ambedkar Marathwada University, Aurangabad 431004 (M.S.), India * Corresponding Author, Email: suhaskamble@rediffmail.com Please Cite This Article As: S.M. Kamble and A.M. Chavan. 2010. Antibacterial Activity of some Fresh Water Algae.J. Exp. Sci. 1(2): 05-06.